MENSTRUAL DISFUNCTIONS INCIDENT AT SWIMMER ATHLETES OF VI BRASILIAN INTERFEDERATIVE SWIMMING CHAMPIONSHIP JUNIOR I AND II (Fiep Bulletin - online, 2015)
Athletic women can present menstrual cycle irregularities, named menstrual disfunctions, have as   form of oligomenorrhea (menstruation scarce or none frequent) and amenorrhea (absence of        around 180 days or more). When menstrual function it's normal receive the name of eumenorrhea (WILMORE e COSTIL, 2001). It prevailing these functions among athletes it's not well documented, therefore the Sandoval´s studies (2002), Baker (1981) e Loucks e Horsvath (1985) they affirm among swimmers the amenorrhea incident is less if compared to ballerinas, long distance runners and gymnastic athletes. Objective: to verify the happening of menstrual dysfunctions at juniors swimmers athletes of categories I and II. Methodology: It was used a sampling of 64 athletes with age between 17 and 19, those ones took part in Swimming Interfederative Brazilian Championship between 8th and 10th of July 2005, at Aquatic Park of UniEVANGÉLICA, city of Anápolis-GO. It was applied a questionnaire to the athletes to evaluate the prevailing of menstrual dysfunctions, as well, sympton and menarche age. Results: 75% of sampling are with eumenorrhea, 21,9% with oligomenorrhea and 3,1% with amenorrhea. 70,3% has pre-menstrual symptom. The average of the menarche it was 12,76 years old with DP of 1,24. Conclusion: the happening of menstrual disturbed at swimmers athletes it was 25% at total. Sampling analyzed, 3,1% had amenorrhea and 21,9% had oligomenorrhea. The percentage of oligomenorréicas swimmers analyzed confered with found at athletic population, showing that have training interference at this dysfunction emergence. The percentage of amenorrhea checked with the one found at general feminine population, proving no interference about training. The average age to menarche presented similar to non-athletes and the main pre-menstrual symptoms described were: irritability, bosom pain, weakness, pelvic pain, headache and legs ache.
Keywords: Swimmers; menstrual dysfunction; menarche.